Enfermedad de Wilson : revisión del tema (2010)
ABSTRACT: Wilson’s disease is an autosomal recessive disorder caused by mutations in the ATP7B gene that lead to an abnormal metabolism of copper, resulting in the accumulation of this element in several organs and tissues. Its diagnosis is based on the combination of the clinical picture with various biochemical tests, neither one of which is, by itself, diagnostic of the disease. Presently there are effective treatments for EW based on the administration of chelating agents to promote mobilization of copper from the accumulation sites and its excretion. Zinc is also used in order to block the intestinal absorption of copper. Liver transplantation is the treatment of choice in patients with fulminating hepatitis, as well as in those with decompensated cirrhosis. This review includes the following aspects of Wilson‘s disease: biochemical, genetic, clinical, diagnostic, and therapeutic.